Climate warming alters competition between two highly invasive alien plant species and dominant native competitors. (15th February 2014) - Verlinden, M; De Boeck, H J; Nijs, I; Clements, David
Summary Biological invasions and climate warming are two major threats to the world's biodiversity. To date, their impacts have largely been considered independently, despite indications that climate warming may increase the success of many invasive alien species. We therefore set up an experiment to study competition between native and invasive alien plant species and the effects of climate warming thereon. Two highly invasive alien plant species in Belgium, each with a native competitor that dominated in invaded sites, were grown either together (1:1 mixtures) or in isolation (monocultures) at ambient and elevated temperature (+3°C) in climate‐controlled chambers. To detect possible mechanisms underlying the effects of competition and elevated temperature, we conducted a combined growth and nitrogen uptake analysis. In one pair, Senecio inaequidens – Plantago lanceolata (alien invasive – native), the alien species dominated in mixture, while in the other pair, Solidago gigantea – Epilobium hirsutum, the native species dominated. Climate warming reduced the invader dominance in the first species pair, but stimulated the suppressed invader in the latter. Many of the biomass responses for these two species pairs could be traced to the root‐specific nitrogen uptake capacity. The responses of the native‐invasive interaction to warming could not always be extrapolated from the monoculture responses, pointing to the necessity for experiments that take into account species interactions.